Синтаксономічні зміни лучної рослинності заплави річки Сейм на території України - Куземко, А.А.; Козир, М.С. (Український ботанічний журнал, 2011)
На основе сравнения описаний луговой растительности, выполненных в 1950—1970-х годах и в настоящее время, выявлены изменения синтаксономического состава в районе поймы Сейма в пределах Украины за последние 50 лет. Увеличилось количество локалитетов, занятых сообществами ассоциаций Koelerio-Agrostietum vinealis, Festuco valesiacae-Ag rostietum vinea lis и Poo trivialis-Alopecuretum pratensis, и соответственно уменьшилось — Poёtum an gus tifoliae, Bromopsidetum inermis и Poo palustris-Alopecuretum pratensis, что свидетельствует о ксерофитизации экотопов. Пастбищная дигрессия обусловила распространение сообществ ассоциаций Festucetum pratensis, Festuco pratensis-Deschampsietum caespitosae, Poёtum pratensis, Anthoxantho-Agrostietum tenuis, Deschampsietum caespitosae, а повышение засоленности почв — ассоциаций Elytrigio repentis-Alopecuretum arundinaceus и Agrostio-Caricetum distantis. Based on comparison of the relevés described in 1950—70s and at present, the changes in syntaxonomic composition of the meadow vegetation on the Seim River floodplain within Ukraine over the 50 years were found. The number of Koelerio—Agrostietum vinealis, Festuco valesiacae—Agrostietum vinealis and Poo trivialis—Alopecuretum pratensis associations localities has increased while Poёtum angustifoliae, Bromopsidetum inermis and Poo palustris-Alopecuretum pratensis associations localities has decreased respectively as a result of xerophytization of the ecotops. The pascual digression results in distribution of communities of associations Festucetum pratensis, Festuco pratensis-Deschampsietum caespitosae, Poёtum pratensis, Anthoxantho—Agrostietum tenuis, Deschampsietum caespitosae and soil salinization causes spreading of the Elytrigio repentis-Alopecuretum arundinaceus and Agrostio-Caricetum distantis communities.